1997
DOI: 10.1038/nbt0297-159
|View full text |Cite
|
Sign up to set email alerts
|

Design and production of novel tetravalent bispecific antibodies

Abstract: We have produced novel bispecific antibodies by fusing the DNA encoding a single chain antibody (ScFv) after the C terminus (CH3-ScFv) or after the hinge (Hinge-ScFv) with an antibody of a different specificity. The fusion protein is expressed by gene transfection in the context of a murine variable region. Transfectomas secrete a homogeneous population of the recombinant antibody with two different specificities, one at the N terminus (anti-dextran) and one at the C terminus (anti-dansyl). The CH3-ScFv antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(149 citation statements)
references
References 27 publications
2
146
0
1
Order By: Relevance
“…S2). The scFv is in the orientation VH-(G 4 S) 4 -VL and has VH 44 and VL 100 residues mutated to cysteine, which form an interdomain disulfide in the scFv designed to improve stability of the scFv. 22 The transient expression levels of Bs4Ab-VA in human embryonic kidney (HEK)293 cells was 150 mg/L, which is similar to that of the parental anti-VEGF and anti-Ang2 antibodies.…”
Section: Examples Of Antibodies Derived From the Bs4ab Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…S2). The scFv is in the orientation VH-(G 4 S) 4 -VL and has VH 44 and VL 100 residues mutated to cysteine, which form an interdomain disulfide in the scFv designed to improve stability of the scFv. 22 The transient expression levels of Bs4Ab-VA in human embryonic kidney (HEK)293 cells was 150 mg/L, which is similar to that of the parental anti-VEGF and anti-Ang2 antibodies.…”
Section: Examples Of Antibodies Derived From the Bs4ab Technologymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Bispecific molecules described thus far can be divided into five classes based on their molecular format: 1) BsAb with IgG1-like structure, which are monovalent for each antigen; 2) BsAb prepared by appending binding domains to the IgG, which are bivalent for each antigen; 3) BsAb prepared using antibody fragments, which are monovalent for each antigen and often lack the Fc region; 4) bispecific fusion proteins, which are formed of an antibody fragment genetically linked to a protein to add additional functionality or specificity; and 5) bispecific conjugates, which are prepared by chemical conjugation of antibody fragments. While some such bispecific molecules have demonstrated manufacturing robustness, in vivo drug-like properties, suitable pharmacokinetics (PK) and efficacy have been achieved, platforms that yield multifunctional bispecific antibodies with different spatial configurations and flexibility suitable for a variety of target and disease applications are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison reported that the anti-DNS scFv possessed high affinity (K D ¼ 1.4 Â 10 À8 M À1 ) for DNS hapten. 35,36 Our result showing that DNS-FITC was retained by B16/DNS cells for at least 10 h indicates that the DNS hapten is stably attached to the DNS receptors. The valency of the DNS-imaging probe was also important for in vivo imaging.…”
Section: Discussionmentioning
confidence: 81%
“…The third class of molecules are appended IgGs with symmetric architecture in which the second binding site is fused to either the IgG heavy or light chain in a symmetrical fashion. 12-15 …”
Section: Introductionmentioning
confidence: 99%